Homolytic Bond Strength and Radical Generation from (1‐Carbomethoxyethyl)pentacarbonylmanganese(I). Issue 39 (28th June 2019) - Morales‐Cerrada, Roberto; Fliedel, Christophe; Gayet, Florence; Ladmiral, Vincent; Améduri, Bruno; Poli, Rinaldo
Abstract : Compound (1‐carbomethoxyethyl)pentacarbonylmanganese(I), [MnR(CO)5 ] (R = CHMeCOOMe, 1 ), was synthesized from K + [Mn(CO)5 ] – and methyl 2‐bromopropionate and isolated in pure form. Upon thermal activation, the Mn–R bond is homolytically cleaved and the resulting 1‐carbomethoxyethyl radical is able to initiate the polymerization of methyl acrylate (MA). A kinetic study of the decomposition of 1 in the presence of tris(trimethylsilyl)silane, TTMSS (10 equiv., saturation conditions) at 70, 65 and 60 °C yielded the T‐dependent activation rate constant, k a, which allowed the calculation of the activation enthalpy (Δ H ‡ = 35.3 ± 2.8 kcal mol –1 ) and entropy (Δ S ‡ = 27.2 ± 8.1 cal mol –1 K –1 ) through the use of the Eyring relationship. The Δ H ‡ value can be taken as an upper limit for the thermodynamic bond dissociation enthalpy, which was estimated as 36.9 kcal mol –1 by DFT calculations. The higher thermal stability of 1 relative to that of simpler R derivatives that form stronger Mn–R bonds can be attributed to more difficult CO dissociation, precluding the decomposition by β‐H elimination. Abstract : The metal‐carbon bond in [Mn(CHMeCOOMe)(CO)5 ] is sufficiently weak to be homolytically cleaved, releasing the acrylate radical under mild conditions (Δ H a ‡ = 35.3 ± 2.8 kcal mol –1, Δ S a ‡ = 27.2 ± 8.1 cal mol –1 K –1 ) to initiate the radical polymerization of methyl acrylate.